2021
DOI: 10.3390/ijerph18042119
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Selected Studies on Predictor Variables Associated with the Malaria Status among Children under Five Years in Sub-Saharan Africa

Abstract: Background/Purpose: In recent times, Sub-Saharan Africa (SSA) had been rated by the World Health Organization (WHO) as the most malaria-endemic region in the world. Evidence synthesis of the factors associated with malaria among children aged under-five in SSA is urgently needed. This would help to inform decisions that policymakers and executors in the region need to make for the effective distribution of scarce palliative resources to curb the spread of the illness. This scoping review is aimed at identifyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…However, Azikiwe et al (2012) found that RDTs and microscopy laboratory investigation of malaria Pf yield similar results with RDTs being more precise [ 55 ]. In addition, in a recent scoping review [ 1 ], RDT was found to be more frequently used in studies compared to microscopic smears. Additionally, in 2018 NDHS, RDTs account for more samples than microscopic blood smear laboratory test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Azikiwe et al (2012) found that RDTs and microscopy laboratory investigation of malaria Pf yield similar results with RDTs being more precise [ 55 ]. In addition, in a recent scoping review [ 1 ], RDT was found to be more frequently used in studies compared to microscopic smears. Additionally, in 2018 NDHS, RDTs account for more samples than microscopic blood smear laboratory test.…”
Section: Discussionmentioning
confidence: 99%
“…The predictor variables considered for this study were identified from previous scoping reviews [ 1 , 30 , 31 ], and categorized in line with previous studies, and as reported in NDHS 2018 final report [ 21 ]. Two files in 2018 NDHS, children under-five years (KR), and household members (PR), were merged using a common identifier to obtain variables that meet this analysis [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictor variables considered for this study were identified from previous scoping reviews [1,27,28]. These variables were grouped into children/individual-related variables to include, child's sex, age, perceived birth size, order, malaria status, nutritional status, fever, acute respiratory infection status, had diarrhoea, duration of breastfeeding, deworming, iron pills/syrup, and child took vitamin A; parental-related to include, place of delivery; preceding birth interval, maternal religious status, age group, age at first birth, educational status, working status, body mass index, anaemia status, autonomy level, marital status, ante-natal care visit, maternal ethnicity, religious status, maternal iron supplement during pregnancy, and paternal education status and work status; others are household-related to include, household socioeconomic status (wealth index), household size, number rooms for sleeping, number of under-five in the household, age and sex of household head, under-five slept under bed net last; and community-related variables to include, household region of residence, place of residence, community distance to health facility; and area-related variables to include, the state multidimensional poverty index, and the state human development index.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Over the last twenty years, malaria has remained a major worldwide public health concern [1], with over 300 million cases reported in 2018 [2] and has remained a leading cause of morbidity and mortality. Low and Medium-Income Countries (LMIC), especially Sub-Sharan Africa (SSA) contributes more than 80% of the global malaria burden [3,4].…”
Section: Introductionmentioning
confidence: 99%